The LHCb trigger and its performance in 2011 - Aaij, Roel; Krocker, Georg Alexander; Stahl, Sascha (Journal of Instrumentation, 2013)
This paper presents the design of the LHCb trigger and its performance on data taken at the LHC in 2011. A principal goal of LHCb is to perform flavour physics measurements, and the trigger is designed to distinguish charm and beauty decays from the light quark background. Using a combination of lepton identification and measurements of the particles' transverse momenta the trigger selects particles originating from charm and beauty hadrons, which typically fly a finite distance before decaying. The trigger reduces the roughly 11 MHz of bunch-bunch crossings that contain at least one inelastic pp interaction to 3 kHz. This reduction takes place in two stages; the first stage is implemented in hardware and the second stage is a software application that runs on a large computer farm. A data-driven method is used to evaluate the performance of the trigger on several charm and beauty decay modes.